A new Approach for experimental evaluation of contact stresses - LUPOI, ROCCO (My University, 2005)
n metal forming operations, t he intensity and distribution o f stresses at the tool/material interface have great influence on the pattern and mode of deformation. This is due to the effect of frictional forces in being resistive to material movements and hence affects material flow and the directionality of volume distribution of material inside die cavities. This paper explores the use of the pressure pin technique for the measurement of tool stresses at the interface between the tool and the deforming workpiece material. It also introduces a new experimental meth odology for the measurement of stresses where the measuring device is concealed inside the tool and not subjected to the severe conditions at the interface surface. Each tool containing measuring devices is split into two parts, one part has the shape to b e formed (industrial die), while the second part includes the pressure pin measuring column. Friction resistance and friction coefficient are evaluated across the billet surface and at different stages of deformation .
AMPT 2005
Keywords: Pressure pin; Interface Friction; Tool Stresses; Contact Stresses